Protective Effects of Vaccinium arctostaphylos L., Berberis thunbergii var. atropurpurea Chenault, Elaeagnus angustifolia L. and Launaea acanthodes (Boiss.) O. Kuntze against Indomethacin-Induced Gastric Ulcers in Rats - H Fallah Huseini; S Kianbakht; M Hoormand (Institue of Medicinal Plants, ACECR, 2013)
Background: Data suggest that V. arctostaphylos, B. thunbergii var. atropurpurea, E. angustifolia and L. acanthodes may prevent gastric ulcers induced by Non-steroidal anti-inflammatory drugs (NSAIDs). Objective: To explore the ulcer-protective potential of these plants in indomethacin-induced gastric ulcers in rats. Methods: Saline, hydro-alcoholic extract of each plant (100, 400, 800 mg/kg) and omeprazole (30 mg/kg) were gavaged to the groups of animals for 4 consecutive days. Gastric ulcers were induced by the onetime gavage of indomethacin (30 mg/kg, p.o.). On the fifth day, each group was pretreated with physiological saline as control, extract (100, 400 or 800 mg/kg, p.o.) or omeprazole (30 mg/kg, p.o.) 30 min before the indomethacin administration. The animals were killed 6 h after the indomethacin administration. The stomachs were removed, opened along the greater curvature and washed in physiological saline. A person unaware of the type of treatment received by the animals examined the stomachs under a 3-fold magnifier. The areas and lengths of hemorrhagic lesions induced by indomethacin were measured using a dial caliper and the sum of measurements for each animal was referred to as the ulcer index. Results: All extracts reduced the ulcer index significantly compared to the control group (p < 0.05). Conclusion: These plants prevent NSAID-induced gastric ulcers in rats. The efficacy and potency of the gastro-protective effect of L. acanthodes appears to be higher than the other 3 plants.